Analysis of Dust Reduction Characteristics of Multistage Tandem Dust Removal System - Jiajun Zhang; Dong Liang; Yuanwen Cao (Shock and Vibration)
Asphalt hot regeneration pavement maintenance vehicle is a type of in situ heating waste asphalt special vehicle equipment for mix and regeneration of aged asphalt. When waste asphalt mixture is heated and melted, a lot of organic fumes are typically produced, along with dust from the mixing process. Because of the complex composition of the exhaust gases produced by asphalt hot regeneration pavement maintenance vehicles, it can be difficult to purify and remove them using a single method. In order to effectively purify exhaust gas with complicated compositions, a multistage combined treatment dust removal system structure is presented that includes cyclone sections, spray sections, and adsorption sections. With an emphasis on the cyclone section structure with the dust-gas separation function, computational fluid dynamics (CFD) is used to analyze the internal flow field characteristics, turbulence intensity, tangential velocity, and velocity field vector characteristics. The results reveal that the more symmetrical the distribution of tangential velocity field and static pressure field is, the greater the cyclone dust collector’s dust removal efficiency is, the more stable the flow field is, and the lower the turbulence intensity is. Furthermore, the center cyclone’s growing speed is adversely connected with dust removal effectiveness. As a result, an antiventuri cyclone dust collector with a scrambling column was designed. When the inlet air speed is 6 m/s, the dust removal efficiency of the improved device is 97.0%, which is 5.1% higher than that of the original device, and when the inlet air speed is 8 m/s, the dust removal efficiency of the improved device is 97.3%, which is 4.16% higher than that of the original device. With the increase of the inlet air speed, the difference between them keeps decreasing.